Anatomy of Love - Kadyrova, Natalia (Russia, 2012)
Two Russian prisons begin an experiment testing the emergence of maternal love. Children under the age of three live with their convicted mothers but only spend two hours a day with them. During these short visits, the mothers do not have enough time to give their heart to their children. So in one prison a baby is allowed to live with his mother full time.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films